OVERVIEW OF RED GINGER BOILED WATER ADMINISTRATION FOR REDUCING PRIMARY DYSMENORRHEA PAIN IN ADOLESCENT GIRLS IN KARANGCENGIS VILLAGE - Bintari, Nufia; Sulistyowati, Priyatin; Priyatin, Wiwik (PT. Jurnal Center Indonesia Publisher, 2025)
Primary dysmenorrhea is menstrual pain commonly experienced by adolescent girls and can disrupt daily activities. One alternative non-pharmacological pain management option is herbal therapy, such as boiled red ginger (Zingiber officinale var. rubrum), which is known to have anti-inflammatory and analgesic properties. Red ginger contains gingerol, an anticoagulant that can inhibit the release of enzymes into prostaglandins, which contribute to inflammation and reduce uterine contractions, thus relieving menstrual pain.To determine the effectiveness of red ginger decoction on adolescent girls with primary dysmenorrhea in the Karangcengis Village area. This study uses a descriptive case study with respondents of adolescent girls with primary dysmenorrhea focusing on the administration of red ginger decoction as a complementary therapy. This study was conducted in Karangcengis Village for 3 days starting from June 23-25, 2025. After administering red ginger decoction for 3 days once a day from the first day of menstruation to the third day of menstruation, the results of the pain scale before being given red ginger decoction reached 6 (moderate pain).After administering 200ml of red ginger decoction once daily in the morning for three days, from the first day of menstruation to the third day, the pain scale decreased to a level 1 (mild pain). Administering red ginger decoction to adolescent girls experiencing dysmenorrhea can reduce the pain.